1993
DOI: 10.1007/bf02918988
|View full text |Cite
|
Sign up to set email alerts
|

Production of cellulolytic and xylanolytic enzymes during growth of anaerobic fungi from ruminant and nonruminant herbivores on different substrates

Abstract: Three anaerobic fungi, two Neocallimastix strains isolated from a ruminant (sheep) and one Piromyces strain isolated from a nonruminant (black rhinoceros), were tested for their ability to ferment a range of substrates. Bagasse, filter paper cellulose, fructose, and wheat straw were good inducers of celluloytic and xylanolytic enzymes. These enzymes were produced constitutively by all three strains, although enzyme activities were generally lower, especially for both Neocallimastix strains, after growth on glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The weakening of plant tissues by fungal enzymes accelerates digestion, making rumination more effective in reducing particle size and increasing protozoal and bacterial digestion in the rumen. Because of the ability of cellulases to rapidly attack crystalline cellulose, there has been considerable interest in the fiber-degrading enzymes of anaerobic fungi (Teunissen et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The weakening of plant tissues by fungal enzymes accelerates digestion, making rumination more effective in reducing particle size and increasing protozoal and bacterial digestion in the rumen. Because of the ability of cellulases to rapidly attack crystalline cellulose, there has been considerable interest in the fiber-degrading enzymes of anaerobic fungi (Teunissen et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…These fungi have been isolated from animals in a range of geographically distinct locations and are typified by their ability to colonise and degrade the recalcitrant cell walls of many wild and cultivated plants, including maize stems, rice and wheat straws, Soya hulls and temperate and tropical grasses [2,[5][6][7][8][9][10]. Anaerobic fungi are known to produce a wide range of extra-cellular, plant cell-wall hydrolysing enzymes including cellulases, hemicellulases and esterases and thus they are very effective degraders of lignocellulosic materials [11][12][13][14]. For example, two isolates (Neocallimastix hurleyensis and an Orpinomyces) were able to degrade up to 60% of the apparent cell-wall biomass of wheat straw when grown in continuous flow cultures containing 80-100 g/L wheat straw dry matter (DM) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic fungi of the class Chytridiomycetes, including members of the genera Neocallimastix and Piromyces, are extremely active digesters of plant cell wall polysaccharides [ 1,2]. Previous reports have shown that true cellulase activity of Neocallimasti frontalis resides in a high molecular weight multiprotein cellulose-binding complex [3,4], composed of 6 polypeptides ranging from 56 kDa to 126 kDa; the complex was very active against crystalline cellulose but differed from the cellulosome of Clostridium thermocellum in containing only a small fraction of the total fungal endoglucanase activity, and appar-ently no xylanase.…”
Section: Introductionmentioning
confidence: 99%